2010
DOI: 10.1002/jmv.21653
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of prevalent G1P[8] human rotaviruses in South Korea

Abstract: The human rotavirus G1P[8] strain is one of the most common rotaviruses worldwide, including Korea. Six Korean G1P[8] human rotaviruses, isolated using cell culture techniques, were characterized on the basis of sequence differences in VP7, VP4, VP6, and NSP4 genes to elucidate the evolutionary relationships in the community. All strains had a long RNA electropherotype, supported by VP6 gene analysis, clearly associated with subgroup II specificity. The phylogenetic analysis of VP7 gene sequences showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
27
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 58 publications
6
27
0
Order By: Relevance
“…Rotavirus G1 genotype has been classified into 11 distinct lineages and 17 sublineages based on amino acids located at different positions [Phan et al, 2007a]. Studies carried out on this genotype have documented circulation of lineage IIA in Italy in the 1990s and lineages IA, ID, and III in Japan and Germany, IIC in Italy, III in Brazil, and IA in Bangladesh in the 2000s among children [Arista et al, 2006; Arau´jo et al, 2007; Phan et al, 2007a; Trinh et al, 2007; Dey et al, 2009a; Le et al, 2010; Pietsch et al, 2011]. The G1 strains recovered from adolescents and adults of the present study persistently showed sublineage specificity of IB and IC at both time points and that of IA only in the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus G1 genotype has been classified into 11 distinct lineages and 17 sublineages based on amino acids located at different positions [Phan et al, 2007a]. Studies carried out on this genotype have documented circulation of lineage IIA in Italy in the 1990s and lineages IA, ID, and III in Japan and Germany, IIC in Italy, III in Brazil, and IA in Bangladesh in the 2000s among children [Arista et al, 2006; Arau´jo et al, 2007; Phan et al, 2007a; Trinh et al, 2007; Dey et al, 2009a; Le et al, 2010; Pietsch et al, 2011]. The G1 strains recovered from adolescents and adults of the present study persistently showed sublineage specificity of IB and IC at both time points and that of IA only in the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, rotavirus is still the most common viral agent of acute diarrhea in young children. Although G1P[8] was the most prevalent strain until 1997 regardless of geographic area or season [6,9], the predominant G type strain has shifted to other genotypes including G4, G2 or G9 [10-13]. In the present study, we examined the diversity of the G and P types of human rotavirus strains isolated in South Korea during 2000 – 2004 periods.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other common strains (G1-G4), which are detected almost exclusively with P [8] or P [4], the G9 strains have been detected with variety of P types, including P [4], P [6], P [8], P [9], P [11], and P [19] [26]. The VP4 sequence analysis indicated that CAU05-202 belonged to the G9P [8] genotype.…”
mentioning
confidence: 99%
“…The presence of rotavirus strains in MA104 cells was determined by indirect immunofluorescence assay and polyacrylamide gel electrophoresis [19].…”
mentioning
confidence: 99%